2023
DOI: 10.1097/inf.0000000000004057
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Antiviral Therapy for Immune-tolerant Hepatitis B Viral Infection in Children: A Systematic Review and Meta-analysis

Fengli Zheng,
Zhijun Tan,
Zhou Liang
et al.

Abstract: Background: Chronic hepatitis B virus (HBV) infection burden in children remains a pressing public health concern. Whether antiviral therapy should be administered to children with HBV in the immune-tolerant phase remains controversial. We performed a meta-analysis to evaluate antiviral therapy efficacy and safety in children with immune-tolerant hepatitis B (ITHB). Methods: A search was conducted in multiple databases (PubMed, Embase, Cochrane, Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…First, our results indicate significantly low rates of HBV DNA negative conversion (0%–2%) and HBsAg loss or seroconversion (0%) in both adult and paediatric untreated patients in the IT phase. This aligns with previous meta‐analyses, 12,13 suggesting that spontaneous achievement of HBV DNA undetectability and HBsAg clearance is rare in patients in the IT phase. However, our data revealed that approximately 4% of patients in the IT phase can spontaneously achieve HBeAg seroconversion within 48–96 weeks of follow‐up, potentially due to phase changes experienced by patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, our results indicate significantly low rates of HBV DNA negative conversion (0%–2%) and HBsAg loss or seroconversion (0%) in both adult and paediatric untreated patients in the IT phase. This aligns with previous meta‐analyses, 12,13 suggesting that spontaneous achievement of HBV DNA undetectability and HBsAg clearance is rare in patients in the IT phase. However, our data revealed that approximately 4% of patients in the IT phase can spontaneously achieve HBeAg seroconversion within 48–96 weeks of follow‐up, potentially due to phase changes experienced by patients.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, Lee et al.’s meta‐analysis 9 comparing outcomes between the IT and IA phases found similar pooled HCC and mortality incidence. Four meta‐analyses 10–13 assessing antiviral therapy efficacy for patients in the IT phase yielded conflicting conclusions due to the lack of a strict IT phase definition, limited cases, and poor article quality. Updated data on patients in the IT phase are crucial for better disease understanding, enabling physicians to develop strategies, increase awareness, and implement interventions to reduce its burden.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al found that the cumulative rate of HBsAg loss was 46% in paediatric patients with immune-active CHB after a median follow-up of 13 years, 3 which was significantly higher than the reported rate (22%-24%) among children with immune-tolerance CHB. 4,5 In addition, we divided the enrolled children into two groups according to their baseline condition, and demonstrated that paediatric patients with CHB in the IC phase had better treatment responses (HBsAg loss: 57.0% vs 27.3%, p < 0.05) than those in the IT phase. Our observations provide a more comprehensive understanding of the effects of treatment on different phases of CHB in children.…”
Section: E T T E R T O T H E E D I T O R Letter: Baseline Age On Anti...mentioning
confidence: 99%
“…It should not be ignored that studies with long observation periods of treated children compared to untreated children have not highlighted major differences in terms of complications and mortality over a period of 24-29 years[ 16 , 17 ]. The other pediatric studies that demonstrated an advantage of the treatment focused heavily on obtaining laboratory objectives rather than the risk of complications from cirrhosis and HCC and duration of survival[ 18 , 19 ]. Thus, as often happens, we run the risk of applying evidence carried out in adulthood to children and therefore medicalizing a group of subjects who may not have significant complications in the long term.…”
Section: Should the Indications For Hbv Treatment Be Expanded?mentioning
confidence: 99%